2005
DOI: 10.1007/s00259-004-1728-1
|View full text |Cite
|
Sign up to set email alerts
|

99mTc-sestamibi thyroid uptake in euthyroid individuals and in patients with autoimmune thyroid disease

Abstract: Five minutes is the optimal time interval between (99m)Tc-sestamibi injection and calculation of thyroid uptake. Five-minute uptake differentiates euthyroid individuals from GD patients. There is a high correlation between (99m)Tc-sestamibi and (99m)Tc-pertechnetate uptake in GD. The reduced (99m)Tc-sestamibi uptake in AHT patients is probably due to glandular destruction and fibrosis. Inflammatory infiltrate and high mitochondrial density in thyrocytes possibly explain the increased uptake in GD and HHT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…The sestamibi's biodistribution is characterized by a rapid blood clearance and early uptake by target organs. 6,7,10 The most accepted mechanism of Tc-99m sestamibi uptake by myocardial cells is based on passive diffusion of the tracer through plasma and mitochondrial membranes. In normal conditions, there is a strong negative transmembrane potential which promotes the tracer concentration in the internal mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The sestamibi's biodistribution is characterized by a rapid blood clearance and early uptake by target organs. 6,7,10 The most accepted mechanism of Tc-99m sestamibi uptake by myocardial cells is based on passive diffusion of the tracer through plasma and mitochondrial membranes. In normal conditions, there is a strong negative transmembrane potential which promotes the tracer concentration in the internal mitochondrial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic alterations can result in decreased Tc-99m sestamibi uptake. 6,7,10,11 The main advantage of the use of Tc-99m sestamibi over 131I-iodine and Tc-99m pertechnetate in thyroid scintigraphy is the thyroid uptake mechanism which is not altered by iodine overload and antithyroid drugs use. Some authors demonstrated that the previous perchlorate intake does not decrease Tc-99m sestamibi uptake, which points out that its uptake is not mediated by the same mechanisms as iodine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Olgulara 370 MBq (10 mCi) Tc-99m MIBI intravenöz yoldan verildi (9). Görüntüleme için çift başlı gama kamera (Infinia, GE Medical Hipotiroidi tablosundaki otoimmun tiroiditli bireylerde tükrük bezi salgı miktarı düşük (%57) saptanırken, hipertiroidili hastalarda tükrük bezi salgı miktarının daha fazla olduğu (%75) belirlenmiştir.…”
Section: Deneysel Modelunclassified